ESBL-producing Gram-negative organisms in the healthcare environment as a source of genetic material for resistance in human infections. Issue 1 (January 2017) - Muzslay, M.; Moore, G.; Alhussaini, N.; Wilson, A.P.R.
Summary: Background: The increasing prevalence of extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae in the healthcare setting and in the community despite established infection control guidelines indicates that these microorganisms may possess survival strategies that allow them to persist in the environment. Aims: To determine the extent and variation in endemic ESBL-carrying species in different ward environments, and to investigate the potential for cephalosporin resistance to be transferred from environmental isolates to human pathogens. Methods: Conventional microbiological methods were used to sample 1436 environmental surfaces for ESBL-producing bacteria. Transconjugation assays (broth mating experiments) were performed using environmental ESBL-producing isolates as donors and streptomycin-resistant Escherichia coli (NCTC 50237) as the recipient. Findings: The prevalence of ESBL-producing bacteria on surfaces in a non-outbreak setting was low (45/1436; 3.1%). The sites most likely to be contaminated were the drains of handwash basins (28/105; 26.7%) and floors (14/160; 8.8%). Fifty-nine ESBL-carrying organisms were isolated. Of these, Klebsiella spp. (33.9%), Enterobacter spp. (20.3%), Pantoea spp. (15.3%) and Citrobacter spp. (13.6%) were the most common isolates. ESBL determinants were transferred successfully from three representative environmental isolates ( Pantoea calida, Klebsiella oxytoca, Raoultella ornithinolytica ) to the human pathogen E. coli . Conclusion: ESBL-producing Gram-negative isolates were recovered from the hospital environment in the absence of any ESBL infection on the wards. The drains of handwash basins should be considered potential long-term reservoirs of multi-drug-resistant bacteria and drug resistance genes. These genes can reside in various genera of hardy environmental organisms and be a potential source of ESBL for more common human pathogens.